Mediaspeak : three American voices - Fox, Roy F. (Praeger, 2001)
This text defines and analyzes the content, structure and values of three predominant types of public discourse, labelled Doublespeak, Salespeak and Sensationspeak. These media messages are examined to determine how they are constructed and how they influence individuals, ideology and culture.